Motivation Profiles for Physical Activity Among Office Workers - Zhong, Tao; Wang, Hui (Frontiers in Psychology, 2019)
Physical activity is of importance for health enhancement. To promote physical activity involvement, motivation is considered to be a key factor. The study aimed to examine the motivation profiles of physical activity in a sample of Chinese office-based workers, grounded in a person-centered approach. Latent profile analysis was performed to generate motivation profiles for physical activity behavior. Successively, profile differences in relation to different motivations and physical activity were explored. Two motivation profiles emerged from the analysis. The two profiles differed significantly in various behavioral motivations and physical activity. The findings indicate that motivation profile characterized by autonomous motivation and introjected regulation is more favorable in physical activity participation, compared with a profile featured by external regulation and amotivation. The motivation profiles naturally emerged are informative for future intervention design aiming to facilitate physical activity participation.